A calculus problem by Hamza A

Calculus Level 4

( lim n 0 π / 2 sin n x + cos n x n d x ) 2 = ? \large\left(\displaystyle\lim _{ n\rightarrow \infty }{ \displaystyle\int _{ 0 }^{ \pi /2 }{ \sqrt [ n ]{ \sin ^{ n }{ x } +\cos ^{ n }{ x } } }\, dx }\right )^{ 2 } =\, ?


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

C Anshul
Jun 29, 2018

Let L = lim n ( s i n x ) n + ( c o s x ) n n L=\displaystyle\lim_{n\rightarrow \infty} {\sqrt[n]{ (sin x)^{n}+(cos x)^{n}}}

L = lim n c o s x 1 + ( t a n x ) n n L=\displaystyle\lim_{n\rightarrow \infty}{cos x}{\sqrt[n]{ 1+(tan x)^{n}}}

Now let L 1 = lim n 1 + ( t a n x ) n n L_{1}=\displaystyle\lim_{n\rightarrow \infty} {\sqrt[n]{ 1+(tan x)^{n}}}

Taking l n ln both sides

l n L 1 = lim n l n ( 1 + tan n x ) n lnL_{1}=\large\displaystyle\lim_{n\rightarrow \infty}\displaystyle\dfrac{ln(1+ \tan^{n}{x})}{n}

for 0 < x < π / 4 , 0 < t a n x < 1 , l n L 1 0<x<π/4 , 0<tan x<1, lnL_{1} goes to 0 hence L 1 L_{1} is 1 and L L is c o s x \large cos x .

For π / 4 < x < π / 2 , t a n x > 1 , l n L 1 π/4<x<π/2 , tan x>1 , lnL_{1} goes to l n t a n x lntan x using L'hopital rule hence L L is c o s x t a n x cos x tan x i.e. L = s i n x L=sin x .

rest work is easy

We get 0 π / 4 \large\displaystyle\int_{0}^{π/4} c o s x d x cos x dx + π / 4 π / 2 \large\displaystyle\int_{π/4}^{π/2} s i n x d x sin x dx

= 1 / 2 + 1 / 2 =1/√2+1/√2

= 2 =√2

John Frank
Apr 12, 2018

Let I = 0 π 2 ( sin n ( x ) + cos n ( x ) ) 1 n d x \displaystyle I = \int_{0}^{\frac{\pi}{2}} (\sin^n(x)+\cos^n(x))^\frac{1}{n} dx .

Let us substitute u = π 2 x u = \frac{\pi}{2} - x . (We find that d x = d u dx = -du .)

I = 0 π 2 ( sin n ( x ) + cos n ( x ) ) 1 n d x = π 2 0 ( sin n ( π 2 u ) + cos n ( π 2 u ) ) 1 n ( d u ) = 0 π 2 ( cos n ( u ) + sin n ( u ) ) 1 n d u = I \begin{aligned} I &= \int_{0}^{\frac{\pi}{2}} (\sin^n(x)+\cos^n(x))^\frac{1}{n} dx \\ &= \int_{\frac{\pi}{2}}^{0} \Big(\sin^n\Big(\frac{\pi}{2} - u\Big) + \cos^n\Big(\frac{\pi}{2} - u\Big)\Big)^\frac{1}{n} (-du) \\ &= \int_{0}^{\frac{\pi}{2}} (\cos^n(u)+\sin^n(u))^\frac{1}{n} du \\ &= I \end{aligned}

We can think of the substitution u = π 2 x u = \frac{\pi}{2} - x as reflecting the graph of ( sin n ( x ) + cos n ( x ) ) 1 n \displaystyle (\sin^n(x)+\cos^n(x))^\frac{1}{n} in the line x = π 4 x=\frac{\pi}{4} . We see that integral does not change. This is because the graph of ( sin n ( x ) + cos n ( x ) ) 1 n \displaystyle (\sin^n(x)+\cos^n(x))^\frac{1}{n} is symmetric along the line x = π 4 x=\frac{\pi}{4} .

Hence, we deduce that I = 2 0 π 4 ( sin n ( x ) + cos n ( x ) ) 1 n d x \displaystyle I = 2\int_{0}^{\frac{\pi}{4}} (\sin^n(x)+\cos^n(x))^\frac{1}{n} dx .

Now, we have to figure out what happens as n n tends to infinity.

I = 2 0 π 4 ( sin n ( x ) + cos n ( x ) ) 1 n d x = 2 0 π 4 cos ( x ) ( tan n ( x ) + 1 ) 1 n d x = 2 0 π 4 cos ( x ) exp ( ln ( 1 + tan n ( x ) ) n ) d x \begin{aligned} I &= 2\int_{0}^{\frac{\pi}{4}} (\sin^n(x)+\cos^n(x))^\frac{1}{n} dx \\ &= 2\int_{0}^{\frac{\pi}{4}} \cos(x)(\tan^n(x)+1)^\frac{1}{n} dx \\ &= 2\int_{0}^{\frac{\pi}{4}} \cos(x)\exp\bigg(\frac{\ln(1+\tan^n(x))}{n}\bigg) dx \end{aligned}

We observe the following chain of implications.

0 x π 4 0 tan ( x ) 1 0 tan n ( x ) 1 where n is a positive real number 1 tan n ( x ) + 1 2 0 ln ( tan n ( x ) + 1 ) ln ( 2 ) since ln ( x ) is a strictly increasing function 0 ln ( 1 + tan n ( x ) ) n ln ( 2 ) n \begin{aligned} 0 \leq x \leq \frac{\pi}{4} & \implies 0 \leq \tan(x) \leq 1 \\ & \implies 0 \leq \tan^n(x) \leq 1 & \text{where } n \text{ is a positive real number} \\ & \implies 1 \leq \tan^n(x) + 1 \leq 2 \\ & \implies 0 \leq \ln(\tan^n(x) + 1) \leq \ln(2) & \text{since } \ln(x) \text{ is a strictly increasing function} \\ & \implies 0 \leq \frac{\ln(1+\tan^n(x))}{n} \leq \frac{\ln(2)}{n} \\ \end{aligned}

We know that lim n 0 = 0 \displaystyle \lim_{n\to\infty} 0 = 0 and lim n ln ( 2 ) n = 0 \displaystyle \lim_{n\to\infty} \frac{\ln(2)}{n} = 0 . Therefore, by the squeeze theorem

lim n ln ( 1 + tan n ( x ) ) n = 0 \lim_{n\to\infty} \frac{\ln(1+\tan^n(x))}{n} = 0

Consequently,

( lim n 2 0 π 4 cos ( x ) exp ( ln ( 1 + tan n ( x ) ) n ) d x ) 2 = ( 2 0 π 4 cos ( x ) exp ( lim n ln ( 1 + tan n ( x ) ) n ) d x ) 2 = ( 2 0 π 4 cos ( x ) d x ) 2 = ( 2 ( 1 2 ) ) 2 = 2 \begin{aligned} \bigg(\lim_{n\to\infty} 2\int_{0}^{\frac{\pi}{4}} \cos(x)\exp\bigg(\frac{\ln(1+\tan^n(x))}{n}\bigg) dx\bigg)^2 &= \bigg(2\int_{0}^{\frac{\pi}{4}} \cos(x)\exp\bigg(\lim_{n\to\infty} \frac{\ln(1+\tan^n(x))}{n} \bigg) dx \bigg)^2 \\ & = \bigg(2\int_{0}^{\frac{\pi}{4}} \cos(x) dx\bigg)^2 \\ &= \Big(2\Big(\frac{1}{\sqrt{2}}\Big)\Big)^2 \\ &= \boxed{2} \end{aligned}

Pranav Bansal
Sep 24, 2017

Take out (cosx)^n from (sinx^n+cosx^n)^(1/n) and break limits at x=π/4 . For x<π/4 , tanx^n<<<<<<.........1 ,(tanx is a proper fraction and n tends to infinity) and for x>π/4 , tanx^n>>>>>>>>>>>>>>>.......1 (tanx is greater than 1 and n tends to infinity). The integral has reduced to : Integral of (cosx from 0 to π/4) + integral of (sinx from π/4 to π/2) = √2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...